What’s Cooking? - Symons, Michael (Petits Propos Culinaires, 2001)
After publishing a gastronomic history of Australia One Continuous Picnic in 1982, and founding the Symposiums of Australian Gastronomy, Michael Symons completed a PhD in the sociology of cuisine. In his new book, A History of Cooks and Cooking, now published by Prospect Books in Great Britain and the University of Illinois in the United States (having been first issued in Australia as The Pudding that Took a Thousand Cooks), he examines the achievements of cooks since they ’first picked up stone kitchen knives’.